PM2.5 components and outpatient visits for asthma: A time-stratified case-crossover study in a suburban area. (December 2017) - Jung, Chau-Ren; Young, Li-Hao; Hsu, Hui-Tsung; Lin, Ming-Yeng; Chen, Yu-Cheng; Hwang, Bing-Fang; Tsai, Perng-Jy
Abstract: The effects of fine particles (PM2.5 ) on asthma have been widely confirmed by epidemiological research studies. However, a limited number of studies have investigated the relationship between exposure to different PM2.5 components and asthma. We characterized the PM2.5 components in a suburban site of central Taiwan and conducted a time-stratified case-crossover study to elaborate the effects of daily concentration of each PM2.5 component on asthma outpatient visits. We retrieved asthma outpatient claims for individuals less than 20 years old with a residential address in the Shalu district, Taiwan, from the National Health Insurance Research Database during 2000–2010. Multiple linear regression models were used to back extrapolate the historic concentration of individual components of PM2.5 from 2000 through to 2010, including black carbon (BC) and eight ions, namely, sulfate, nitrate (NO3 − ), ammonium, chloride, potassium (K + ), magnesium, calcium, sodium. The odds ratio (OR) with a 95% confidence interval (CI) of individual PM2.5 components on asthma was estimated by conditional logistic regression. A total of 887 asthma outpatient visits with individuals who have an average age of 7.96 ± 3.88 years were selected. After adjusting for confounders, we found an interquartile range (IQR) increase in BC level, an IQR increase in NO3 − level, and an IQR increase in K + level that were all associated with the increased risk of asthma outpatient visits from the current day (OR = 1.18, 95% CI: 1.05–1.34; OR = 1.11, 95% CI: 1.01–1.21; and OR = 1.16, 95% CI: 1.04–1.30, respectively). The effects of these components on asthma were stronger in the cold season than in the warm season. However, we did not find any lagging effects. The results suggest that exposure to NO3 −, BC, and K + derived from industry-related combustion or motor vehicles emission sources may increase the risk of asthma outpatient visits, particularly during the cold season. Graphical abstract: Highlights: Historic PM2.5 components can be extrapolated by multiple linear regressions. Short-term exposures to NO3 −, BC, and K + are associated with asthma outpatient visits. The effects of PM2.5 components on asthma were strong in the cold season. There are linear exposure-response relationships between NO 3−, BC, K +, and asthma. Our finding suggests no lagged effects of PM2.5 components on asthma outpatient visits.